Feasibility Study of Concave Wing Design for Subsonic Aircraft (NACA 2412) - Singh, Tarminder; Asmuin, Norzelawati (Progress in Aerospace and Aviation Technology, 2022)
In this current world of technology, airfoil has been produced in many different shapes in terms of root size, tip size, existence of winglet and different thickness. Above all other criteria to create the best airfoil, the aerodynamics of the airfoil is the most significant aspect that need to be considered when modelling an airfoil. Using wing morphing concept, tendency of wing to bend at a certain height of deflection due to increase of lift force. Using SolidWorks, the wing can be modelled and run flow simulation to determine the optimum height of deflection. In this study, 0.2 metre deflection shows the highest lift coefficient and lift drag ratio compared to other height of deflection. The maximum value of Cl obtained is 1.517, while for Cl/Cd is 37.708